Systemic Failure of Subsidized Gas Distribution from the Perspective of Economic Analysis of Law - Mulyadi M (Media Hukum Indonesia (MHI), 2026)
This study aims to conduct an in-depth analysis of systemic failures in the distribution chain of 3-kilogram Liquefied Petroleum Gas (LPG) in the Jakarta metropolitan area, particularly in response to global energy price shocks in 2026. Using an interdisciplinary Economic Analysis of Law (EAL) framework, this research evaluates the incentive structures that drive distribution irregularities, including interregional allocation leakages and large-scale illegal gas adulteration practices. The main focus is directed at three critical variables: (1) disparities in non-harmonized regional Maximum Retail Prices (HET), (2) policies restricting base-level quota volumes that overlook the Decent Living Needs Standard (KHL) in Jakarta, and (3) the increase in non-PSO LPG prices as of April 18, 2026, triggered by the Strait of Hormuz crisis as a primary catalyst for economic crime. Through the application of Rational Choice Theory, Deterrence Theory, and the Coase Theorem, this study identifies that distribution irregularities represent rational responses by economic actors to regulatory inefficiencies. The findings indicate that punitive approaches through criminal law enforcement entail very high administrative costs and relatively low effectiveness compared to administrative measures such as price harmonization and targeted distribution digitalization. The analysis underscores the need to reassess the quota/allocation restrictions of 2,000 to 3,000 cylinders per month for distribution bases.